Tunable magnetic and electronic properties of armchair BeN4 nanoribbons. Issue 6 (26th January 2023) - Zhu, Mingrui; Zhou, Wanxin; Yang, Jiangtao; Zhou, Jian; Li, Qingfang
Abstract : BeN4 nanoribbons demonstrate various magnetic configurations (AFM, FM, and FIM) and rich electronic properties including semiconductor, nearly half-metallic, and metallic characters. Abstract : Recently, layered BeN4 as a novel Dirac semimetal has been fabricated (M. Bykov, T. Fedotenko, S. Chariton et al. Phys. Rev. Lett ., 2021, 126, 175501). Motivated by the experiment, we perform first-principles calculations to predict the stability, magnetic configurations, and electronic structures of unsaturated BeN4 nanoribbons with an armchair-terminated edge. The magnetic interactions and electronic properties of BeN4 nanoribbons are sensitively influenced by the edge morphology. The BeN4 nanoribbons with both edges occupied by Be atoms undergo a transition from a ferromagnetic (FM) metal to an antiferromagnetic (AFM) semiconductor with the increase of ribbon width. The configurations with edges situated by Be and N atoms are FM/ferrimagnetic (FIM) metals or nearly half-metals, and the spin polarizability is as high as 85% when the ribbon width is N = 5. The nanoribbons with both edge sites occupied by pentagonal N atoms are nonmagnetic (NM), while the nanoribbons terminated by N atoms in a hexagonal ring are FM metals. We also explore the magnetic properties and band structures of BeN4 nanoribbons with hydrogen passivation. Our results open up a versatile edge engineering avenue to design BeN4 -based spintronic and nanoelectronic devices.